Dampak Perubahan Kebijakan Izin Mendirikan Bangunan (IMB) Menjadi Persetujuan Bangunan Gedung (PBG) di Kabupaten Padang Pariaman - Maggara, Tomi Satria; Frinaldi, Aldri (AHKAM, 2023)
The aim of writing this article is to see the impact of changing the building construction permit (IMB) policy to building construction approval (PBG) in Padang Pariaman Regency. Law Number 23 of 2014 concerning Regional Government states that the management of buildings in the regions is part of the implementation of government affairs in the field of public works and spatial planning which is the authority of the Regency/City government. This article applies a qualitative method by applying a descriptive analysis system in presenting it. The data collection technique for this research is a library research library study sourced from various reading literature and previous research articles regarding policy implementation. There are still obstacles in granting Building Approvals in Padang Pariaman Regency, lack of public awareness of the importance of PBG, lack of public understanding of the procedures and requirements for PBG applications through the SIMBG system and limited professional technical planning staff.